2022
DOI: 10.3390/su14042319
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality and the Flipped Classroom—A Comparative Analysis of University Student Motivation in Semi-Presence-Based Education Due to COVID-19: A Pilot Study

Abstract: Background: This study aims to analyze university student motivation during the period of semi-presence-based education due to the COVID-19 pandemic, based on the type of educational material used: Augmented Reality (AR) videos and traditional videos associated with the Flipped Classroom (FC) methodology. Methods: A sample of 129 university students were asked to take the Instructional Materials Motivation Survey (IMMS). Results indicate that participants in the study were generally more motivated by AR educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In agreement with studies by earlier authors in which the flipped classroom method was applied (Alebrahim & Ku, 2020;Campos-Mesa, 2022;Zhu, Lian & Engström, 2020), what has been verified here is an improvement in academic performance on the module, in this case of almost one extra point on a ten-point scale when comparing the academic results obtained in the module's final exam between the students who participated in this experiment and those who did not. This can be attributed to an increase in hours dedicated to learning with increased daily effort and attention (Salcines-Talledo, Cifrián-Bemposta, González-Fernández & Viguri-Fuente, 2020), to the commitment and central role of the students (Miragall & García-Soriano, 2016) and to the fact that the teacher prepared videos explaining the topic and providing additional material for study, helping to involve students fully in the learning process.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with studies by earlier authors in which the flipped classroom method was applied (Alebrahim & Ku, 2020;Campos-Mesa, 2022;Zhu, Lian & Engström, 2020), what has been verified here is an improvement in academic performance on the module, in this case of almost one extra point on a ten-point scale when comparing the academic results obtained in the module's final exam between the students who participated in this experiment and those who did not. This can be attributed to an increase in hours dedicated to learning with increased daily effort and attention (Salcines-Talledo, Cifrián-Bemposta, González-Fernández & Viguri-Fuente, 2020), to the commitment and central role of the students (Miragall & García-Soriano, 2016) and to the fact that the teacher prepared videos explaining the topic and providing additional material for study, helping to involve students fully in the learning process.…”
Section: Discussionsupporting
confidence: 93%
“…Consequently, there are numerous recent relevant works, such as those done by Aguilera, Manzano, Martínez, Lozano and Casiano (2017), Alebrahim andKu (2020), Prieto, Diaz, Lara, Monserrat, Sanvicen, Santiago et al (2018), Romero-García, de Paz-Lugo, Buzón-García and Navarro-Asencio (2021), Tse, Choi andTang (2019), Valero, Martinez, Pozo andPlanas (2019), ; Zheng, Bhagat, Zhen and Zhang (2020) and Zheng, Chang, Lin and Zhang (2021). This is especially notable since the suspension of in-person classes owing to the Covid-19 pandemic and the shift to online learning in many centres (Campos-Mesa, Castañeda-Vázquez, Del Castillo-Andrés & González-Campos, 2022;Clark, Kaw, Lou & Scott, 2022;Oliván-Blázquez, Aguilar-Latorre, Gascón-Santos, Gómez-Poyato, Valero-Errazu, Magallón-Botaya et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It is among the data obtained from the study that the flipped classroom model increases student motivation. Studies have also shown that materials presented to students and well-defined tasks motivate students (Campos-Mesa, Castañeda-Vázquez, DelCastillo-Andrés and González-Campos, 2022). Within this scope, it is possible to…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 97%
“…Before the Covid-19 pandemic, a survey amongst dental and medical students has already shown students' preference for virtual learning over traditional methods [15]. Studies have also demonstrated that AR provided a motivational drive during remote learning [16]. A scoping review of 21 articles indicated that professionals and students from different medical specialities trained via VR demonstrated a higher level of accuracy in their medical practice [17].…”
Section: Ar and Vr Applications In Higher Educationmentioning
confidence: 99%